Characterization of Trichoderma reesei endoglucanase displayed on the Saccharomyces cerevisiae cell surface and its effect on wine flavor in combination with β-glucosidase. (January 2023) - Huang, Rong; Zhang, Fangfang; Zhou, Hong; Yu, Hongfei; Shen, Lei; Jiang, Jiao; Qin, Yi; Liu, Yanlin; Song, Yuyang
Abstract: This study aimed to achieve the immobilization of endoglucanase (EGII) from the cellulase family on the cell surface of Saccharomyces cerevisiae, and to evaluate the effect of its co-immobilized β- glucosidase (BGL) on volatiles in wine. Trichoderma reesei EGII (encoded by the EGL2 gene) displayed on S. cerevisiae cell surface was obtained by constructing the gene cassettes containing the GPD promoter and glycosylphosphatidylinositol (GPI) anchoring region ( SED1 ). Our results suggested that EGII activity was further enhanced by transcriptional fusion partner (TFP) and host diploid optimization. Diploid-positive transformants displaying BGL and EGII were inoculated at different ratios into synthetic medium MS300 with grape skins to simulate wine maceration fermentation. The effects of the native signal peptide of EGL2 gene and the 24 TFP factors of S. cerevisiae on the EGII enzymatic activity were compared, and the screened EGII under 6-α TFP factor has the highest enzyme activity. Besides, the mixed fermentation of surface-display EGII and BGL significantly increased the content of compounds such as isoamyl alcohol, phenylethyl alcohol, medium-chain fatty acids, acetate and ethyl esters. Therefore, the yeast cell surface display system created a whole-cell biocatalyst and provided insight into the enological practice on the enrichment of typical flavor compounds in wine. Graphical Abstract: ga1 Highlights: Comparison of the efficiency of 24 TFPs (transcriptional fusion partner) and native signal peptide mediated surface display of EGII (endoglucanase) in yeast. Evaluated the effect of haploid and diploid hosts on yeast surface display EGII activity. Display of EGII on yeast cell surface increased ethanol tolerance of the strain. Co-fermentation of yeast surface display EGII and BGL ( β -glycosidase) enhances wine aroma compounds.